Unique geological objects of Tomsk region: textbook - Rychkova I. V. Irina Vladimirovna (Tomsk, TPU Publishing House, 2025)
This textbook serves as a guide to the most interesting geological objects of Tomsk region, as Lagerniy Sad/Camp Garden, Anikino Rocks and Siniy Utyos/Blue Cliff. All photographs, except for those specially noted, are the author’s. The fossils presented in the photographs are original author’s findings which are stored in the funds of TPU Paleontological Museum. The textbook can be useful in studying the discipline "Professional foreign language" for students of geological specialties and who deliver some study in the scope of "Applied Geology" and have educational geological practice in the vicinity of Tomsk. In addition, this information is of great use to the international students and master degree program students, who have practice at these geological outcrops, and many young geologists, guests of Tomsk and Tomsk region from other countries who are interested in local history and geology and who arrive to Tomsk for the purpose of educational tourism